THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ON COMPANY FINANCIAL PERFORMANCE AND FIRM VALUE (An Empirical Study on the Manufacturing Companies Listed at Indonesia Stock Exchange (IDX) in 2011) - Vidiananda, Gabriela; Saraswati, Erwin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The objective of this research is to observe the influence of Corporate Social Responsibility (CSR) to financial performance and firm value. The company financial performance is measured by using Return on Asset (ROA) and firm value is measured by Tobinâ€™s Q. This research applies two control variables, those are: SIZE and leverage. As the samples of this research are 69 manufacturing companies listed at Indonesia Stock Exchange (IDX) in 2011 that are obtainedÂ by using purposive judgment sampling method. The testing result with multiple linear regression test shows that Company Social Responsibility (CSR) has influence to company financial performance and firm value. The analysis result also show that SIZE as a control variable does not give influence to financial performance but it influence firm value. On the other hand, leverage as a variable control gives influence to both financial performance and firm value. Â Keywords: Corporate Social Responsibility, financial performance, firm value, SIZE, leverage.